Teologi Keagamaan Kwok Pui-lan: Dari Hermeneutika Asia Menuju Keadilan Gender (Sebuah Peta Pemikiran Teologi Kontekstual Asia) - Andreas Kristianto (KENOSIS: Jurnal Kajian Teologi, 2022)
This study refers to Kwok Pui-lan's thoughts on her shift from religious pluralism to gender justice in Asia. Asia experiences a syndrome known as the colonial syndrome, so that postcolonial hermeneutics is needed in the life of the church. The main ideas are as follows, namely a shift from Western hermeneutics to Asian hermeneutics (dialogical interpretation model), from textual interpretation to oral hermeneutics, from Asian interpretation to religious pluralism (multifaith hermeneutics) and from religious pluralism to gender justice. Kwok Pui-lan's theology brings dimensions of intersectionality (cross) between colonialism, gender and religion, which is a fresh material to build a postcolonial theology of religious and gender diversity in Indonesia. The contribution of this article is that Kwok Pui-lan's thoughts build awareness of “multiplicity”, namely about the existence of many identities and layers of domination from the analysis of colonial history, race, class, culture, sexual orientation and gender.Abstrak Studi ini merujuk pada pemikiran Kwok Pui-lan tentang pergeserannya dari Pluralisme agama menuju keadilan gender di Asia. Asia mengalami sindrom yang disebut sebagai sindrom kolonial, sehingga dibutuhkan hermeneutika postkolonial dalam kehidupan menggereja. Pokok-pokok pemikirannya adalah sebagai berikut yaitu adanya pergeseran dari hermeneutika Barat menuju hermeneutika Asia (model penafsiran dialogis), dari intepretasi tekstual menuju hermeneutika lisan (oral), dari intepretasi Asia menuju pluralisme agama (multifaith hermeneutics) dan dari pluralisme agama menuju keadilan gender. Teologi keagamaan Kwok Pui-lan membawa dimensi interseksionalitas (persilangan) antara kolonialisme, gender dan agama, yang mana menjadi bahan segar untuk membangun teologi postkolonialisme di Indonesia. Kontribusi artikel ini adalah bahwa pemikiran Kwok Pui-lan membangun kesadaran akan “multiplisitas”, yaitu adanya banyak identitas dan lapisan dominasi dari analisis sejarah kolonial, ras, kelas, budaya, orientasi seksual dan gender.